log base 5 of x = lnx/ln5
Using I = integral
1/ln5 is a constant so I(lnx/ln5) = (1/ln5)I(lnx)
Now I(lnx) = xlnx - x + C
So answer is (xlnx-x+C)/ln5
2006-12-25 14:37:52
·
answer #1
·
answered by Andy 2
·
0⤊
2⤋
So you want to solve
Integral (log [base 5](x)dx
As others have pointed out, you want to use the Change of Base formula to convert this. Recall that the change of base formula goes as follows:
log[base c](a) = log[base b](a) / log[base b])(c)
This implies we can choose a new base from an old base. In our case, what we want to choose is base e. This would give us
log[base 5](x) = log[base e](x) / log[base e](5)
and log[base e] is defined to be ln, so
log[base 5](x) = ln(x) / ln(5) = [1/ln(5)] ln(x)
Therefore,
Integral (log[base 5](x))dx = Integral ( [1/ln(5)] ln(x) )dx
When solving any integral, it's best to pull out constants.
[1/ln(5)] * Integral (ln(x))dx
And now we solve the integral of ln(x) using integration by parts.
Let u = ln(x). dv = dx
du = (1/x) dx. v = x
The result of integrating by parts would give us uv - Integral (v du)
[1/ln(5)] { xln(x) - Integral ( (1/x)x )dx }
Note that (1/x) times x is equal to 1.
[1/ln(5)] {xln(x) - Integral (1) dx }
Giving us the solution
[1/ln(5)] {xln(x) - x} + C
Expanding this out,
x ln(x)/ln(5) - x/ln(5) + C
2006-12-25 23:59:02
·
answer #2
·
answered by Puggy 7
·
1⤊
0⤋
hmm... try integration by parts. Consider the integrand to be 1 * log_5 (x) and then set...
u = log_5 (x)
dv = 1 dx
And see where that takes you.
Or, as suggested above, use the change of base formula to make it ln (x) / ln_e (x). Then pull out 1 / ln_e (x) as a constant in front of the integral sign and you are left with the integral of ln (x). If you use the integration by parts trick I mentioned above (by looking at it as 1 * ln (x) ) then it will work out.
2006-12-25 22:39:24
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
the answer is 1/(xln5)
you take the antiderivative of x (which is 1) and put that over the natural log of the base of the log (ln5) times x.
I hope that makes sense.
2006-12-25 22:39:49
·
answer #4
·
answered by bpsfm_2004 2
·
0⤊
2⤋
y= f(x) = log base 5 of x
This is the same as saying:
5^y =x
So ln 5^y = ln x
y ln 5 = ln x
y=(ln x)/(ln 5)
integ y = f(x) = integ (ln x)/(ln 5)
=(1/ln 5) integ ln x
= (1/ln 5)91/x) + C
2006-12-25 23:54:01
·
answer #5
·
answered by ironduke8159 7
·
1⤊
1⤋
â«lnx/ln5 dx
=(1/ln5)(xlnx - â«dx) (integration by parts)
=(1/ln5)(xlnx - x) + c
2006-12-25 22:55:57
·
answer #6
·
answered by sahsjing 7
·
1⤊
0⤋
plesae visit this link for quick solution:
http://calc101.com/parts_2.html
2006-12-26 00:34:14
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
http://www.public.iastate.edu/~aaallen/Mat165-E1Fa05/Mat165Ch7Formulas.pdf
2006-12-25 22:55:31
·
answer #8
·
answered by James 2
·
1⤊
0⤋